Pengaruh konsentrasi bahan pengental terhadap karakteristik nori analog dari daun binahong (Anredera cordifolia) - Hermawan Seftiono; Syahidah Syahidah; Moh Taufik (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Nori is one of the products that are in demand by the people of Indonesia. Nori is mostly a product that is imported and produced by foreign companies. The price of seaweed, the raw material for making nori, is relatively expensive, so it is necessary to diversify the raw materials for making nori. This study aimed to determine the effect of thickener concentration on the organoleptic properties, chemical properties and physical properties of nori analog from binahong leaves. Organoleptic tests yielded the two best formulas, namely F3 (80% binahong leaves and 20% sago) and F6 (85% binahong leaves and 15% sago). Furthermore, chemical and physical analysis was carried out. The results of chemical analysis on the nori analog showed that analog nori F3 and F6 had a moisture content of 5.72% and 6.84%, an ash content of 4.27% and 5.21%, protein content of 3.66% and 4.60 %, fat content of 9.06% and 8.90% and carbohydrate content values of 77.29% and 74.45%. Physical analysis of analog nori included analysis of texture, color, and thickness. The hardness value of nori on F3 was 2.13 gf, while on F6 it was 2.15 gf. Color of nori analog of F3 and F6 obtained 50.44 and 49.38, with a lighter green color for F3 compared to F6, which produced a darker green color. The thickness values of the F3 and F6 analog nori obtained were 0.92 mm and 0.64 mm.